Formation of cubic Li2TiO3 by mechanical activation and its transformation to monoclinic phase: Stability in helium and hydrogen flows - Carbajal Ramos, Ines Alejandra; Andrade Gamboa, Julio José; Condo, Adriana Maria; Gennari, Fabiana Cristina (Elsevier Science, 2017)
Fil: Carbajal Ramos, Ines Alejandra. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte; Argentina. Comisión Nacional de Energía Atómica. Gerencia del Área de Energía Nuclear. Instituto Balseiro; Argentina. Comisión Nacional de Energía Atómica. Centro Atómico Bariloche; Argentina